UMP now known as Universiti Malaysia Pahang Al-Sultan Abdullah - MCI, Eng (Malaysia China Insight, 2023)
KUANTAN, July 30 — After 21 years of its inception, Universiti Malaysia Pahang (UMP) is now rebranded as Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), said its vice-chancellor Professor Datuk Dr Yuserrie Zainuddin.